AMINO ACID PROFILE OF EARTHWORM AND EARTHWORM MEAL (Lumbricus rubellus) FOR ANIMAL FEEDSTUFF - Istiqomah, L.; Sofyan, A.; Damayanti, E.; Julendra, H. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
Earthworm meal (Lumbricus rubellus) has become one of natural material that could be used asfeed additive. Powdering method of earthworm was done by using formic acid addition. The study wascarried out (1) to evaluate the essential amino acid profile of earthworm and earthworm meal, (2) tocalculate the value of essential amino acid index (EAAI) of both materials. A modified EAAI equationwas developed from the essential amino acid profile of earthworm and earthworm meal. The resultshowed that essential amino acid of earthworm was dominated by histidine (0.63% of dry matter basis),meanwhile the earthworm meal was dominated by isoleucine (1.98% of dry matter basis). The nonessential amino acid of earthworm and earthworm meal was dominated by glutamic acid (1.52% and3.60% of dry matter basis respectively). The value of essential amino acid index obtained fromearthworm meal was higher (58.67%) than those from earthworm (21.23%). It is concluded thatpowdering method of earthworm by using formic acid addition had higher amino acid balance thanearthworm.